Analisis pelaksanaan pengawasan dan panerapan standar operasional secara maksimal terhadap kualitas pekerja karyawan PT nutri inti prima perkasa - Agus Bambang Nugraha; Ramlawati Ramlawati; Ahmad Yudhira; Khamo Waruwu (JRTI (Jurnal Riset Tindakan Indonesia), 2022)
The purpose of this study was to determine the effect of Supervision and Implementation of Operational Standards on the Quality of Work of Employees of PT Nutri Inti Prima Perkasa Medan. This research was conducted at PT Nutri Inti Prima Perkasa Medan, with a population and sample of 56 people taken by purposive sampling. The research instrument is a questionnaire/questionnaire with a Likert scale model. Requirements test was conducted to test for normality. The data analysis technique used is multiple regression technique at a significance level of = 0.05. The results showed: there was a positive but not significant effect between supervision (X1) on work quality with t count = 1.376 < t table 2.004 and a significant value of 0.175>0.05. While the variable Implementation of Operational Standards (X2) on Work Quality with a value of t count = 3.093 > t table 2.004 with a significant level of 0.003> 0.05 based on the results of SPSS output it is known that the R square value of 0.216 or 21.6% means the Supervision factor and Operational Implementation can be explained by Quality of Work, while the rest can be explained by other factors such as performance, incentives, leadership style, training and organization of 78.4%.